HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT PENGETAHUAN PERAWATAN PENDERITA SKIZOFRENIA DI KLINIK JIWA RSD MANGUSADA BADUNG - Cahyaningsih, Nur; Susila, I Made Dwie Pradnya (Poltekkes Kemenkes Medan, 2021)
Schizophrenic patients have decreased ability to maintain daily care. Family support in the care of schizophrenic patients is influenced by the knowledge of schizophrenic patient care by the family which can give a positive response in daily care for schizophrenic patients. This study aimed at determining the correlation between family support and the level of knowledge in the care of schizophrenics at the Mental Clinic of RSD Mangusada Badung. The study was implemented with an analytic observational design with a cross-sectional approach. The total samples were 67 respondents using the incidental sampling technique. Data were collected using a family support questionnaire and a questionnaire on the level of care knowledge. Data were analyzed using Spearman`s rho test. The results of the study were 36 people with adequate family support with a percentage of 53.7% and 36 people with a high level of knowledge of care with a percentage of 53.7%. correlation analysis between family support and the level of knowledge of care obtained p-value <0.001. There was a correlation between family support and the level of knowledge of schizophrenic care in Mental Clinic RSD Mangusada Badung. The recommendations of this study are expected to be input for nurses to always provide care education for schizophrenia patients to their families.